Glutamate promotes neural stem cell proliferation by increasing the expression of vascular endothelial growth factor of astrocytes in vitro - Liu, C X; Xu, X; Chen, X L; Yang, P B; Zhang, J S; Liu, Y (Cellular and Molecular Biology, 2015)
The high levels of glutamate might involve in neurogenesis after brain injuries. However, the mechanisms are not fully understood. In this study, we investigated the effect of glutamate on the proliferation of rat embryonic neural stem/progenitor cells (NSCs) through regulating the vascular endothelial growth factor (VEGF) expression of astrocytes (ASTs) in vitro, and the cyclin D1 expression of NSCs. The results showed that glutamate promoted the expression and secretion of VEGF of rat astrocytes by activating group I mGluRs. Astrocyte conditioned medium-containing Glu [ACM (30%)] promoted the proliferation of embryonic NSCs compared with normal astrocyte conditioned medium+Glu [N-ACM (30%)+Glu (30 Î¼M)] by increasing cell activity, diameter of neurospheres, bromodeoxyuridine (BrdU) incorporation and cell division; while ACM+VEGF neutralizing antibody [ACM (30%)+VEGF NAb (15 Î¼g/ml)] significantly inhibited the proliferation of embryonic NSCs compared with ACM (30%). ACM (30%) increased the expressions of cyclin D1 and decreased cell death compared with N-ACM (30%)+Glu (30 Î¼M). ACM (30%)+VEGF NAb (15 Î¼g/ml) decreased the expressions of cyclin D1 and increased cell death compared with ACM (30%). These results demonstrated that glutamate could also indirectly promote the proliferation of rat embryonic NSCs through inducing the VEGF expression of ASTs in vitro, and VEGF may increase the expression of cyclin D1. These finding suggest that glutamate may be a major molecule for regulating embryonic NSC proliferation and facilitate neural repair in the process of NSC transplants after brain injuries.